A survey of video behavior recognition based on deep learning - Duoduo ZHAO; Jianwu ZHANG; Chunsheng GUO; Di ZHOU; ABDUSHARAFALHAKIMI MOHAMMED (Dianxin kexue)
In recent years,the deep learning method of automatic learning features has been continuously explored in the field of video behavior recognition.The traditional behavior recognition methods and the underlying principles of deep learning were outlined.Then a number of behavior recognition methods based on different input content and different deep networks was compared and analyzed.Finally,the development of deep learning in the field of behavior recognition was concluded and its future development trend was prospected.